The Association of Serum Bilirubin on Kidney Clinicopathologic Features and Renal Outcome in Patients with Diabetic Nephropathy: A Biopsy-Based Study - Wu, Yucheng; Zhang, Junlin; Wang, Jiali; Wang, Yiting; Han, Qianqian; Li, Hanyu; Wang, Tingli; Liu, Fang (Endocrine practice, 2019)
To explore the relationship between serum bilirubin concentration and clinicopathologic features and renal outcome in biopsy-diagnosed diabetic nephropathy (DN) in patients with type 2 diabetes mellitus. In this retrospective study, 118 patients with DN were enrolled. Participants were divided into two groups according to their median baseline serum bilirubin concentration: Group 1 (serum bilirubin ≤7.5 μmol /L); Group 2 (serum bilirubin >7.5 μmol /L). Basic clinical parameters were measured at the time of renal biopsy, and the relationships between serum bilirubin and the clinicopathologic features and renal outcome were analyzed. Patients in Group 1 often had inferior renal function. Compared with Group 2, the glomerular classification and interstitial inflammation were more severe in subjects of Group 1, while arteriolar hyalinosis and interstitial fibrosis and tubular atrophy (IFTA) were comparable between the groups. Serum bilirubin was negatively correlated with the severity of the glomerular classification, interstitial inflammation, and IFTA. In the prognostic analysis, higher serum bilirubin level was associated with a lower risk of progression to end-stage renal disease, which was independent of the effects of age, gender, duration of diabetes, anemia, serum glucose, and hypertension but not of estimated glomerular filtration rate (hazard ratio, 0.406; 95% confidence interval, 0.074 to 2.225; = .299). Our study showed a negative correlation between serum bilirubin level and renal pathologic lesions in patients with DN; serum bilirubin showed an inverse association with DN progression, but this was not independent. = confidence interval; = chronic kidney disease; = diabetes mellitus; = diabetic nephropathy; = diabetic retinopathy; = estimated glomerular filtration rate; = end-stage renal disease; = glycated hemoglobin; = heme oxygenase 1; = hazard ratio; = interstitial fibrosis and tubular atrophy; = log-transformed baseline serum bilirubin; = type 2 diabetes mellitus.